Topology is the Principal Determinant in the Folding of a Complex All-alpha Greek Key Death Domain from Human FADD - Steward, Annette (Elsevier, 2009)
In order to elucidate the relative importance of secondary structure and topology in determining folding mechanism, we have carried out a phi-value analysis of the death domain (DD) from human FADD. FADD DD is a 100 amino acid domain consisting of six anti-parallel alpha helices arranged in a Greek key structure. We asked how does the folding of this domain compare with that of (a) other all-alpha-helical proteins and (b) other Greek key proteins? Is the folding pathway determined mainly by secondary structure or is topology the principal determinant? Our Φ-value analysis reveals a striking resemblance to the all-beta Greek key immunoglobulin-like domains. Both fold via diffuse transition states and, importantly, long-range interactions between the four central elements of secondary structure are established in the transition state. The elements of secondary structure that are less tightly associated with the central core are less well packed in both cases. Topology appears to be the dominant factor in determining the pathway of folding in all Greek key domains.